Impact of Genital Hygiene Awareness on Adolescent Girls in Public Schools, Karachi: Behavioral and Influencing Factors (Quasi-Experimental Study) - Pardhan , Shahla; Khan, Khairunnisa; Khalid, Samra; Noorzamin, Iqra; Abro, Murk; Batool, Iqra; Aslam, Hina; Mendhrani, Srikant; Bano, Nazneen (Biological and Clinical Sciences Research Journal, 2025)
Genital hygiene encompasses a range of personal care practices essential for maintaining the urogenital health of adolescent girls. Inadequate knowledge and improper hygiene behaviors can lead to increased susceptibility to infections, reproductive tract diseases, and compromised reproductive health, particularly in resource-limited settings such as Pakistan. Objective: To determine the impact of awareness on genital hygiene behavior and its associated factors among girls studying in secondary schools in Karachi, Pakistan. Methods: A quasi-experimental pre-post intervention study was conducted at a higher secondary school in Karachi, Pakistan, from July 2024 to February 2025. A purposive sampling technique was employed to recruit participants. Data were collected using a structured, pre-tested questionnaire after obtaining formal permission from school authorities. The intervention included an awareness session on genital hygiene. The collected data were coded, tabulated, and analyzed using SPSS. Socio-demographic characteristics were described, and the Wilcoxon signed-rank test was applied to assess changes in hygiene behaviors before and after the intervention. Statistical significance was considered at p < 0.05. Results: Most participants were aged 15–16 (53%). Most fathers had incomplete or completed primary education, whereas mothers were likelier to have attained secondary or higher education. About 56% of the families reported income below their household expenses. Post-intervention results showed a statistically significant improvement in genital hygiene practices, including regular sanitary pads during menstruation, daily bathing, frequent changing of cotton undergarments, and proper drying of the genital area after washing (p < 0.05). Conclusion: The findings highlight the critical role of school-based awareness interventions in improving genital hygiene behaviors among adolescent girls. Educational programs tailored to address reproductive health and hygiene can empower young females and enhance their health outcomes.